Practical possibilities in using q SOFA scale by Emergency Medical Teams - Piękoś, Dominika; Stachowicz, Aleksandra; Sobczyk, Gabriela; Ozga, Dorota (Journal of Education, Health and Sport, 2018)
Sepsis is a life-threatening dysfunction of the body that causes a host to respond incorrectly to an infection. Sepsis and septic shock are a major health issue affecting millions of people each year worldwide. Every fourth person with sepsis dies. Multi-organ trauma, acute myocardial infarction or stroke, early diagnosis and management in the first hours after the onset of sepsis improve survival rate. The Sequential Organ Failure Assessment (SOFA) scale is mainly used to assess sepsis. SOFA helps medical staff to assess the risk of morbidity and mortality due to sepsis. The basic parameters of SOFA are: assessment of the respiratory system based on partial oxygen pressure in the blood (PaO2), assessment of the nervous system based on the Glasgow Coma scale (GCS), assessment of the cardiovascular system based on the average blood pressure or after vasopressor administration (any dose), assessment of liver function based on the level of bilirubin in the blood, assessment of kidney function based on the level of creatinine in the urine, assessment of blood clotting based on the amount of thrombocytes contained in the plasma. This scale is used in hospital settings. qSOFA (Quick Sequential Organ Failure Assessment score) is a simplified version of the SOFA score as the first way to identify high-risk patients due to poor results associated with infection. qSOFA simplifies the SOFA score drastically, taking into account only three clinical criteria and introducing "any change" instead of requiring GCS ≤13. It uses three criteria, assigning one point for low blood pressure (SBP ≤100 mmHg), high respiratory rate (≥ 22 breaths per minute) or changed mentation (GCS <15). qSOFA is a predictor of mortality, not a diagnostic test for sepsis.